A real-time energy management control strategy for battery and supercapacitor hybrid energy storage systems of pure electric vehicles. (October 2020) - Zhang, Qiao; Wang, Lijia; Li, Gang; Liu, Yan
Highlights: A novel energy management strategy based on a combination of wavelet transform, neural network and fuzzy logic. The proposed strategy can deal with amplitude and variation of battery power simultaneously. The proposed strategy has good real-time performance and validated based on a 72V hardware platform. Abstract: Hybrid energy storage systems have attracted more and more interests due to their improved performances compared with sole energy source in system efficiency and battery lifetime. This study aims to propose a real-time energy management control strategy for achieving these goals. The strategy is based on a combination of wavelet transform, neural network and fuzzy logic. Wavelet transform is an effective tool in extracting different frequency components of load power demand to match the characteristics of battery and supercapacitor. However, it is hard to be directly applied in a real-time system. For this, a neural network model, which is offline trained using the dataset obtained from the wavelet transform decomposition, is developed to online predict the low frequency power demand for the battery. Accordingly, the high frequency power demand is online calculated and distributed to the supercapacitor. In addition, a fuzzy logic based supervisory controller is further developed for controlling the supercapacitor voltage within a certain suitable range. Finally, a 72 V battery and 96 V supercapacitor hybrid energy storage system real-time hardware platform has been developed to validate the effectiveness of the proposed energy management control strategy.